Heinrich Hahn (1605-1668): a portrait of a Lutheran jurist at the University of Helmstedt - Astorri, Paolo (Zeitschrift der Savigny-Stiftung für Rechtsgeschichte. Kanonistische Abteilung, 2022)
This article provides a first sketch of the scholarly and confessional identity of the Helmstedt law professor, Heinrich Hahn (1605-1668). It analyses Hahn’s most important work, a commentary on the Paratitla by Matthaeus Wesenbeck (1531-1586), and a funeral sermon delivered by Balthasar Cellarius (1614-1689) at Hahn’s funeral. By exploring what Hahn’s work reveals about his religious convictions alongside Cellarius’ portrait of him, the article presents a paradigmatic model of the interaction between law and religion in the early modern period. In his commentary, Hahn employs Scholastic moral theology, both at the level of general principles and in the resolution of legal problems. However, when it comes to decisive doctrinal points, Hahn turns away from Catholic sources. In the sermon, Cellarius presents Hahn as an ideal law professor whose faith was the foundation of his professional ethos as well as his private life. Throughout the sermon, he questions whether jurists can be good Christians and negotiates the relationship between faith and works.